Detection and Classification of Muskox Habitat on Banks Island, Northwest Territories, Canada, Using Landsat Thematic Mapper Data - Ferguson, Robert S. (ARCTIC, 1991)
The feasibility of using Landsat Thematic Mapper data for mapping muskox summer habitat was tested on northern Banks Island, Northwest Territories. Digital image enhancement and classification techniques were examined to determine if summer foraging habitats could be detected and mapped using Thematic Mapper imagery. Interpretations of the satellite data were verified in the field during the summers of 1988 and 1989. The most important summer foraging habitats for muskoxen included the wet sedge meadow, graminoid tundra and graminoid/dwarf shrub tundra cover types. These lowland habitats were generally distinguishable on enhanced colour images and were easily differentiated from upland areas. The most suitable colour composite for differentiating muskox summer habitats was the near-infrared (band 4), shortwave infrared (band 5) and red (band 3) spectral bands displayed in red, green and blue respectively. Upland cover types, including dwarf shrub tundra, hummocky tundra and dwarf shrub/lichen barrens, were more difficult to differentiate because of spectral variability resulting from differences in plant cover and site characteristics. The classified image had an overall accuracy of 88%. The summer habitats of particular importance to muskoxen had classification accuracies of 84-89%. Detection of important foraging habitats on Thematic Mapper imagery is attributable to the spectral distinctiveness of wet graminoid communities and the high spectral sensitivity and spatial resolution of the infrared sensors, which allow detection of differences in surface moisture and vegetation physiognomy.Key words: bison habitat, boreal forest, digital image analysis, supervised classification, Landsat Thematic Mapper data, habitat mapping, Bison bison athubuscue, remote sensing Mots clés: habitat du bison, foret boréale, analyse d’images numériques, classification numérique, données obtenues à l'aide de l’appareil de cartographie thématique Landsat, île Banks, cartographie de l’habitat, Ovibos moschatus, environnement ...